A novel cationic cobalt(III) Schiff base complex: Preparation, crystal structure, Hirshfeld surface analysis, antimicrobial activities and molecular docking. (December 2017) - Yousef Ebrahimipour, S.; Machura, Barbara; Mohamadi, Maryam; Khaleghi, Moj
Abstract: A novel Co(III) complex, [Co(L)(Imi)3 ]Cl incorporating 2-((3-methoxy-2-oxidobenzylidene)amino)-4-methylphenolate (L 2− ), as a dibasic deprotonated Schiff base ligand and imidazole (Imi) was synthesized and fully characterized using physicochemical and spectroscopic techniques including elemental analysis, conductance measurement, FT-IR, UV–Vis and X-ray single crystal diffraction. As the conductivity data showed, the synthesized complex had a 1:1 ionic nature. The structure of the complex was found to be distorted octahedral in which, O/N donor atoms of the Schiff base ligand and N atoms of three imidazole groups were involved. Antimicrobial activity of the Co(III) complex as well as the its parent Schiff base ligand against two Gram-positive bacteria ( S. Aureus and M. luteus ), two Gram-negative bacteria ( E. coli and P. aeruginosa ) and a fungus ( C. Albicans ) was studied. Moreover, the antimicrobial activity of [Co(L)(Imi)3 ]Cl was investigated using molecular docking of the complex with GlcN-6-P synthase. Graphical abstract: Highlights: A novel cationic mixed-ligand Co(III) Schiff base complex was synthesized and fully characterized. The structure of the complex was determined using X-ray single crystal diffraction. Hirshfeld surface analysis were performed to explore inter-molecular interactions. The antimicrobial activities of the synthesized compounds investigated experimentally and theoretically.